Implementatio of The Innovation Learning Development Design Model from Jerrold E. Kemp, Gary R. Morrison, And Steven M. Ross: Literature Review and Current Implementation - Dunia Purnama; Rina Martiana; Satutik Rahayu (CATHA SAINTIFICA, 2025)
This article reviews the instructional design model developed by Jerrold E. Kemp, Gary R. Morrison, and Steven M. Ross, focusing on its structure, characteristics, and implementation in contemporary educational contexts. The study uses a systematic literature review approach to evaluate how the model responds to the demands of modern education, including the learner-centered philosophy, differentiated instruction, and the integration of digital technologies. The Kemp-Morrison-Ross model features nine interdependent components that can be accessed non-linearly, offering high flexibility and adaptability for instructional planning. The findings indicate that this model aligns well with current curriculum reforms such as Indonesia's Merdeka Curriculum, supporting personalized and project-based learning approaches. Although conceptually robust, challenges exist in practical implementation, such as limited teacher capacity, lack of systemic support, and uneven access to instructional technology. The discussion suggests that this model can serve as a framework for transformative instructional design when supported by adequate training, policy, and digital infrastructure. The article concludes by highlighting the model's potential in guiding instructional innovation and calls for further empirical research to evaluate its effectiveness in diverse learning environments.